Dubrovnik by Tadijanović : a space of intimate in the service of the eternal - Lazibat, Tonći (Array, 2019)
From the very beginnings of its founding, the city has had a great significance: started as the center of social life, in a diachronic sense it has become a place of gathering of different centers of power, the public space, as well as the space of the private - by weaving collective and individual memory into it. The latter is recognized in Tadijanović’s Poems of Dubrovnik, a collection of fourteen poems for which the poet finds inspiration in the Town of Poets, over and over again, during the seventy- years time span. It is the city he loved from the very first moment, but in which he was loved as well, thus he often comes back in his thoughts, linking past, present and future. We have highlighted the four phases of his writing inspired by the Eternal City and have related the theme-motive background with the poet’s age. It is noticed that, in relation to the youthful and playful first love, the worries, the enthusiasm and the exhilaration, his later lyric is pervaded by philosophical concerns about the meaning of life, death, transience and the life’s drab, but he does not therefor diminish the importance of Dubrovnik. With his first and last poem he creates a kind of alpha and omega of his Dubrovnik opus, signifying Dubrovnik as one perfectly finished mindset, by its cyclical reminding on the circle and thus on the reproducibility of the life cycle: birth - life - death - rebirth (through re-readings of poems, in the poet’s case).